Prevalence of Rickettsia species phylotype G022 and Rickettsia tillamookensis in Ixodes pacificus nymphs and adults from Northern California - Erin Trent; Andrea Swei; Tina Feiszli; Megan E.M. Saunders; Jianmin Zhong (Ticks and Tick-Borne Diseases)
Ticks are known vectors of various pathogenic bacteria, including species of Rickettsia. Two novel Rickettsia species have been identified in adult Ixodes pacificus: Rickettsia species phylotype G022 in 2011 and R. tillamookensis in 2021. Currently, the pathogenic potential of these species found in I. pacificus remains unknown. This study aimed to determine the prevalence of phylotype G022 and R. tillamookensis in I. pacificus nymphs across different mean annual temperature and relative humidity zones in California. Adult ticks were also tested for phylotype G022. Ticks were collected from multiple locations in seven northern California counties and tested by real-time PCR. The overall prevalence of phylotype G022 and R. tillamookensis in nymphs (n = 550) was 5.3 % (95 % CI = 3.7 %-7.5 %) and 1.6 % (95 % CI=0.8 %–3.3 %), respectively. The overall prevalence of phylotype G022 in adult I. pacificus (n = 720) was 9.0 % (95 % CI = 7.2 %-11.3 %). Phylotype G022 infects nymphal I. pacificus across a broad geographic range. The prevalence of phylotype G022 was higher in the 11.7–13.3 °C (53–56°F) temperature zone, at 6.4 % (95 % CI = 4.5 %-9.2 %), compared to the 13.9–15 °C (57–59°F) zone, where the prevalence was 0.8 % (95 % CI = 0.2 %-4.6 %). In contrast, the prevalence of R. tillamookensis did not show a statistically significant difference between the two temperature zones, with 1.9 % (95 % CI = 0.9 %-4.1 % in the 11.7–13.3 °C (53–56°F) zone and 0.9 % (95 % CI = 0.2 %-4.9 %) in the 13.9–15 °C (57–59°F) zone. The detection of phylotype G022 in both questing nymphs and adults of I. pacificus suggests that it is transmitted transstadially. qPCR testing revealed no coinfections of G022 and R. tillamookensis in any of the nymphs. Although R. tillamookensis exhibited a lower overall prevalence in nymphs compared to phylotype G022, both bacteria exhibited a similar geographic distribution.